International Political Economy: The Interaction of Politics and Economics in the Global Market - Budiana, Muhammad (Yayasan Pendidikan Belajar Berdikari, 2024)
This research analyzes the interaction between politics and economics in the global market, focusing on the impact of political decisions on international trade dynamics. This study uses the International Political Economy (EPI) approach and examines four main case studies: the United States-China trade war, the European Union's trade policy, the role of multinational corporations in developing countries, and the impact of economic sanctions on Russia and Iran. Through the use of the theories of Mercantilism, Liberalism, and Marxism, the study found that protectionist political policies often create instability in global trade, while liberal approaches promote economic integration and more sustainable growth. In addition, multinational corporations in developing countries often capitalize on economic inequality, and economic sanctions have a short-term impact but do not always produce the desired political change. The results of this study emphasize the importance of a balance between national interests and international cooperation to achieve global economic stability.